2023
DOI: 10.1021/acsomega.3c02645
|View full text |Cite
|
Sign up to set email alerts
|

Study on Coal Wettability under Different Gas Environments Based on the Adsorption Energy

Abstract: Coal seam water injection is a kind of comprehensive prevention and control measure to avoid gas outburst and coal dust disasters. However, the gas adsorbed in the coal seriously influence the coal-water wetting effect. With the deepening of coal seam mining, the gas pressure also gradually increases, but there is still a lack of in-depth understanding of the coal-water wetting characteristics under the high-pressure adsorbed gas environment. Therefore, the mechanism of coal-water contact angle under different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Hydrogen bonds, as the main driving force behind the adsorption behavior of water molecules on coal surfaces, are formed by the electrostatic interaction of a hydrogen atom bonded to one atom of the pair having a high affinity for electrons (typically F, N, or O) . Polar oxygen-containing functional groups on the surface (especially hydroxyl groups) bond with hydrogen atoms in water molecules (polar) in the form of hydrogen bonds through dipole forces to minimize the Gibbs energy of the system, and then Lewis acid–base interaction forces stronger than van der Waals forces are formed between polar molecules . Notably, the hydrogen bonds formed between oxygen-containing functional groups and water molecules are stronger than those between water molecules .…”
Section: Discussionmentioning
confidence: 99%
“…Hydrogen bonds, as the main driving force behind the adsorption behavior of water molecules on coal surfaces, are formed by the electrostatic interaction of a hydrogen atom bonded to one atom of the pair having a high affinity for electrons (typically F, N, or O) . Polar oxygen-containing functional groups on the surface (especially hydroxyl groups) bond with hydrogen atoms in water molecules (polar) in the form of hydrogen bonds through dipole forces to minimize the Gibbs energy of the system, and then Lewis acid–base interaction forces stronger than van der Waals forces are formed between polar molecules . Notably, the hydrogen bonds formed between oxygen-containing functional groups and water molecules are stronger than those between water molecules .…”
Section: Discussionmentioning
confidence: 99%
“…Although the contact angle has been studied under pressured-gas conditions for a long time, the mathematical expression in Equation ( 1) is addressed for the first time in this study [24,30,44].…”
Section: Surface Roughnessmentioning
confidence: 99%
“…Arif et al [27] tested the contact angles of different coal rank samples under CO 2 pressures of 0-20 MPa and found that the contact angles of the different coal ranks increased with an increasing CO 2 pressure. A research group tested the coal-water contact angles of different-rank coal under CH 4 , N 2 , CO 2 , and He pressures of 0-2 MPa [28][29][30]. They found that, as the gas pressure increased, the contact angles all increased, the higher the coal rank, the stronger the gas adsorption and the greater the increase in contact angle.…”
Section: Introductionmentioning
confidence: 99%